The Influence Of Ethical Ideology And Professional Commitment On Ethical Judgement - Rinto Syahdan; Meliana Meliana; Livi Meiga Puteri; Asril Anwar (UNIVED Press, 2025)
This study aims to determine the impact of ethical ideology, auditor experience, and professional commitment on ethical judgment. The target population consists of all auditors from the BPKP in North Maluku Province. A census technique was employed to select the sample for this study. The research utilized quantitative data, primarily obtained from responses to questionnaires filled out by participants. Data collection was conducted through a survey method involving the distribution of these questionnaires. The analysis was carried out using multiple regression techniques. The findings indicate that ethical ideology (specifically idealism) positively influences ethical judgment, while ethical ideology (relativism) negatively affects ethical judgment. Additionally, professional commitment positively impacts the ethical judgment of BPKP auditors in North Maluku Province.